Telematic improvisation with Dime Ensemble / ChaosOrchestra - Koutsomichalis, Marinos (My University, 2026)
Telematic improvisation with Dime Ensemble / ChaosOrchestra, also featuring Marinos Koutsomichalis and students from Cyprus University of Technology for Piksel Festival, Bergen. https://20.piksel.no/2020/11/21/dime-ensemble-concert-between-nantes-bergen-and-lima/